New onset atrial fibrillation in STEMI patients: main prognostic factors and clinical outcome. (14th October 2021) - Barbieri, L; Dal Zotto, B; Tumminello, G; Saviano, M; Gentile, D; Lucreziotti, S; Frattini, L; Tarricone, D; Carugo, S
Abstract: Background: New onset atrial fibrillation (NOAF) is not a so rare condition among patients hospitalized for ST-segment elevation myocardial infarction (STEMI). Several studies showed that NOAF during an acute coronary syndrome (ACS) leads to increased mortality, both at short and long term. The indications for the treatment of patients with known AF undergoing percutaneous coronary interventions (PCI) are clear, while less is available about the management of NOAF during ACS and in particular during STEMI. The purpose of this study is therefore to evaluate mortality and clinical outcome of this high risk subgroup of patients. Methods: We analysed 1455 consecutive patients undergoing coronary angiography and/or PCI for STEMI. CHA2DS2-VASc and HAS-BLED scores were calculated for all patients. In-hospital, 1-year and long-term follow up mortality was evaluated for all patients. Cerebral ischemic and hemorrhagic events were also evaluated as clinical endpoints at 1 year. Results: NOAF was detected in 102 subjects, 62.7% males, with a mean age of 74.8±10.6 years. We found a high prevalence of main cardiovascular risk factors such as hypertension, dyslipidemia, smoke and renal failure. Mean ejection fraction (EF) was 43.5±12.1% and the mean atrial volume was increased (58±20.9 ml). The most represented type of MI at admission was anterior STEMI (46%). NOAF occurred mainly in the peri-acute phase and had a very variable duration (8.1±12.5 min). During hospitalization all patients were treated with Enoxaparin, but only 25.2% of them were discharged with long term oral anticoagulation (16.7% warfarin, 4.9% direct oral anticoagulant). The majority of patients had a CHA2DS2-VASc score >2 and a HAS-BLED score of 2 or 3. In-hospital mortality was 14.2%, while 1-year mortality was 17.2% and long term mortality 32.1% (median follow-up time 1820 days, range 341 to 3985). Through a logistic regression analysis we identified age as an independent predictor of mortality both at short and long term follow up, while EF was the only independent predictor for in-hospital mortality and arrhythmia duration for 1-year mortality. At 1-year follow up we recorded three ischemic strokes, while no bleeding complications. Conclusions: STEMI patients who develop NOAF are a very high-risk population and are characterized by increased short and long term mortality. NOAF should be diagnosed and treated as soon as possible with a correct indication to long term OAC based on the ratio between ischemic and hemorrhagic risk. FUNDunding Acknowledgement: Type of funding sources: None.